HBR's 10 must reads for executive teams. (HBR's 10 must reads (Series), 2023)
"As part of an executive team, you wear many hats. Not only are you responsible for working with other senior leaders to establish strategic goals for the organization and ensure their execution, but you're making tough decisions, shaping organizational culture, and communicating regularly with employees. If you read nothing else on working effectively as a member of an executive team, read these 10 articles. We've combed through hundreds of Harvard Business Review articles and selected the most important ones to help you understand what's required of you as a senior leader so you can set your team and organization up for success. This book will inspire you to: Build the qualities you need as a senior leader in your company; assemble a group that will think boldly and work harmoniously; feel confident while making strategic decisions as a team; avoid common traps when managing risk; help newly hired executives adapt quickly to the organization; and grow talent throughout the company, especially in underrepresented groups"--